(3aUd ef cJGH GdYXeIs - (3CHh YHO Gddg GdMGQK Hf CSO GdeMGSHj, GdMGQK GdeMGSHj,J (B243 (3g` s
(3ChdgG (B:s
(3aEf bGd bGFd ef GdLGgdjf bO JHjf HeG hUaJ CfG hLejY GdGTjGA eMOKhf s
(3BNQgG (B:s
(3heG JbOe ef UaJg hfYJg hJUOjb ai GdcJH GdNGdjI GdefRdI ef YfO Gddg s
(3Vef eLehY , JQJjHgG (B: 3s
(3hHBNQg aUd ef cJGH GdJfHjg Ydi CYeGd GdbdhH ai GdOdGdI Ydi GdhMOGfjI ddeMGSHi ai fUa UaMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B517s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs